Polyolefin soluble polyisobutylene oligomer‐bound metallophthalocyanine and azo dye additives. Issue 4 (30th November 2013) - Priyadarshani, Nilusha; Benzine, Chase W.; Cassidy, Benjamin; Suriboot, Jakkrit; Liu, Peng; Sue, Hung‐Jue; Bergbreiter, David E.
ABSTRACT Metallophthalocyanines prepared with polyisobutyl (PIB) substituents have very high solubility in organic solvents including saturated hydrocarbons, toluene, and other low polarity organic solvents. In heptane, PIB‐bound metallophthalocyanines have solubility of about 0.1 g/mL at 25 °C, solubility values that are significantly higher than other substituted metallophthalocyanines. PIB terminally functionalized with metallophthalocyanines as well as PIB containing terminal azo dye groups also dissolve in molten hydrocarbon polymers like polyethylene or polypropylene. Thus, these highly chromogenic PIB‐bound dyes can be incorporated uniformly into the polyolefins to form colored polymer solids on cooling. Because only a low concentration of a highly hydrocarbon compatible dye is used, the crystallinity and thermal properties of the colored polyolefin products are not significantly affected. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2014, 52, 545–551